Desain Pembelajaran Dick and Carey dan Implementasinya pada Pembelajaran IPA - Askar, Askar; Djono, Djono (Educatio, 2025)
This research investigates the Dick and Carey model and its application in science using a literature review methodology. The Dick and Carey model is a systematic framework comprising ten steps for designing, developing, and evaluating educational programs. This literature review gathers and examines a range of sources from relevant journals, books, and articles. The findings indicate that this model effectively enhances student engagement, understanding of concepts, and learning outcomes in science. Implementing the Dick and Carey model assists educators in designing structured lessons that prioritize educational objectives. Moreover, this model facilitates the creation of teaching materials tailored to student needs and curricular requirements. The research concludes that the Dick and Carey model can be effectively implemented in science education, positively impacting the quality of learning.